Natural Selection Equally Supports the Human Tendencies in Subordination and Domination: A Genome-Wide Study With in silico Confirmation and in vivo Validation in Mice - Chadaeva, Irina; Ponomarenko, Petr; Rasskazov, Dmitry; Sharypova, Ekaterina; Kashina, Elena; Kleshchev, Maxim; Ponomarenko, Mikhail; Naumenko, Vladimir; Savinkova, Ludmila; Kolchanov, Nikolay; Osadchuk, Ludmila; Osadchuk, Alexandr (Frontiers in Genetics, 2019)
We proposed the following heuristic decision-making rule: “IF {an excess of a protein relating to the nervous system is an experimentally known physiological marker of low pain sensitivity, fast postinjury recovery, or aggressive, risk/novelty-seeking, anestheticlike, or similar agonistic-intolerant behavior} AND IF {a single nucleotide polymorphism (SNP) causes overexpression of the gene encoding this protein} THEN {this SNP can be a SNP marker of the bias in dominance} WHILE {underexpression corresponds to subordination} AND vice versa.” Using this decision-making rule, we analyzed 231 human genes of neuropeptidergic, non-neuropeptidergic, and neurotrophinergic systems that encode neurotrophic and growth factors, interleukins, neurotransmitters, receptors, transporters, and enzymes. These proteins are known as key factors of human social behavior. We analyzed all the 5052 SNPs within the 70 bp promoter region upstream of the position where the protein-coding transcript starts, which were retrieved from databases Ensembl and dbSNP using our previously created public Web service SNP_TATA_Comparator (beehive.bionet.nsc.ru/cgi-bin/mgs/tatascan/start.pl). This promoter region contains all the known TATA-binding protein (TBP)-binding sites. As a result, we found 556 and 552 candidate SNP markers of the human bias in dominance and subordination. On this basis, we determined that 231 human genes under study are subject to natural selection against underexpression (significance p < 0.0005), which equally supports the human bias in domination and subordination such as the norm of a reaction (plasticity) of the human social hierarchy. That is why, using mice as an animal model of human inheritance, we found that both domination and subordination biases are inherited from generation to generation from parents to offspring. Our results equally fit both sides of the century-old unsettled scientific debate on whether both aggressiveness and the social hierarchy among humans are caused by genetic inheritance (e.g., Freud and Lorenz) or by nongenetic social education from childhood to the oldest age (e.g., Berkowitz and Fromm).